The Role of Social Counseling in Mitigating the Psychological Impact of Climate Change Anxiety among Young Adults: A Cross-Cultural Comparative Study - Alimuddin, Nurwahida; Gusnarib, Gusnarib; Adam, Adam; Rahmi, Siti; Zaki, Amin (International Journal of Research in Counseling, 2025)
Climate change has emerged as a significant global challenge that profoundly impacts various aspects of life, particularly mental health, and this is especially true for young adults who often experience heightened anxiety and distress in response to environmental changes. The present study investigates the role of social counseling as a vital intervention in mitigating the psychological effects of climate change anxiety. By employing a cross-cultural comparative approach, the research engages participants from diverse cultural backgrounds, allowing for a nuanced understanding of how social counseling practices can be effectively adapted to meet the unique needs of different populations. Findings underscore that effective counseling interventions encompass essential components such as providing emotional support, educating individuals about climate change, and fostering the development of coping skills, all of which not only assist individuals in managing their anxiety but also empower them to take proactive measures regarding their environmental concerns. Furthermore, the study highlights the importance of culturally sensitive methodologies in designing counseling programs, as varying cultural contexts significantly influence perceptions of climate change and responses to anxiety. In light of these insights, the research advocates for integrated strategies that consider cultural nuances when addressing climate change anxiety, thereby offering valuable guidance for mental health practitioners, educators, and policymakers. By fostering resilience among young individuals and recognizing the intersection between environmental issues and mental health, the study contributes to a growing body of literature that calls for holistic approaches to support the mental well-being of future generations as they navigate the complexities of an ever-changing environment.